Classifying chemoreceptors: quantity versus quality - Underbakke, Eric S (Nature Publishing Group, 2010)
This issue of The EMBO Journal features significant novel insight into bacterial chemotaxis. Work from the Sourjik lab reveals that chemoeffectors should be grouped into direct or indirect receptor binders. They also report that distinct functional properties associate with this binding mechanism.